A 220 GHz Orthogonal Modulator Based on Subharmonic Mixers Using Anti‐Paralleled Schottky Diodes. Issue 3 (1st May 2022) - HE, Yue; LIU, Ge; LIU, Juan; LIN, Changxing; SU, Wei
Abstract : In this paper, A 220 GHz orthogonal modulator based on two symmetrical subharmonic mixers is designed, analyzed and measured, where the mixers are implemented basde on antiparallel Schottky diodes. The orthogonal modulator consists of a 90° phase shifted 220 GHz 3 dB coupler, two sub‐harmonically pumped mixers and an in‐phase 110 GHz 3 dB power divider. The IF output signals are in‐phase (I) branch and quadrature (Q) branch operating from DC±3.5GHz. In the back to back experimentaltests, it is shown that the conversion loss of the two 220 GHz I/Q mixers is less than 30 dB when the IF operating frequency is DC−3.5 GHz, IF input power is −10 dBm and the LO power is around 6 mW. Based on floating‐point simulation, the amplitude and phase imbalance of the I/Q mixer are less than 0.2 dB and 2 degree respectively. When the 220 GHz modulator and demodulator are set in a back to back configuration, a signal‐to‐noise ratio of 21 dB can be obtained using the 16QAM modulation type.